RNF43 R117fs mutant positively regulates Wnt/β-catenin signaling by failing to internalize FZD expressed on the cell surface - A-Ri Cho; Hee Jung Sul; Yoo Jin Kim; Bohyun Kim; Dae Young Zang (Scientific Reports, 2022)
Abstract RING finger protein 43 (RNF43) encodes the transmembrane E3 ubiquitin ligase, which targets the Wnt receptor Frizzled (FZD). RNF43 mutations have been discovered in various human cancers including colon, pancreatic, stomach, ovarian, and liver cancers. Functional studies on RNF43 missense mutations have shown that they negatively regulate Wnt signaling; however, there are few functional studies on RNF43 frameshift mutations. In this study, we showed that R117fs and P441fs mutants enhanced Wnt/β-catenin signaling, whereas Q409fs and G659fs mutants retained the ability to suppress Wnt/β-catenin signaling. Specifically, R117fs was unable to ubiquitinate FZD5 due to lack of the RING domain, although it was able to interact with FZD5. Immunofluorescence showed that R117fs failed to internalize FZD5 expressed on the cell surface. We also showed that LGK974, a potent Wnt inhibitor, decreased the Wnt/β-catenin activity by R117fs and P441fs mutations. Together, these results demonstrate that RNF43 frameshift mutations retain normal functionality; thus, targeted anti-cancer therapy can be developed according to the mutation type of RNF43.